The effect of role conflict, role ambiguity, and role overload in burnout government internal supervisors with tri hita karana culture as moderation - Pratiwi, Ida Yuni; Ratnadi, Ni Made Dwi; Suprasto, Herkulanus Bambang; Sujana, I Ketut (International research journal of management, IT and social sciences, 2019)
This study aims to obtain empirical evidence of Tri Hita Karana’s cultural abilities in moderating the effect of role conflict, role ambiguity, and the role overload in burnout experienced by the Government Internal Supervisory Apparatus (APIP) at the Inspectorate of Bali Province. The technique of determining the sample used is saturated sampling (census). The number of respondents was 47 APIP. The data used is in the form of primary data. Data collection using survey methods using questionnaires. The analysis technique used in this study is Partial Least Square (PLS). The results of the analysis show that the culture of Tri Hita Karana causes the effect of role conflict and the role of overload in reduced burnout. However, Tri Hita Karana’s culture does not moderate the effect of the role ambiguity on burnout experienced by the APIP at the Inspectorate of Bali Province.